A Cybersecurity Approach for Evaluating Mobile Agents. Issue 2 (3rd April 2017) - Adegbite, G. A.; Emuoyibofarhe, O. J.; Ajala, F. A.; Awokola, J. A.
ABSTRACT: Security is a significant concern for mobile agent-based computing as mobile agents are vulnerable to malicious hosts and rogue agents. Existing models developed to secure agents, were not essentially evaluated to guarantee the desired level of security. Hence, this work aimed at implementing a cybersecurity approach for evaluating mobile agents using a web-based penetration testing tool called Lens.